Fine needle aspiration biopsy in the diagnosis of neck masses - Raposo, Diogo (2021)
Objective: To evaluate the diagnostic performance of fine needle aspiration biopsy (FNAB) in the diagnosis of neck masses. Study design: Retrospective study. Materials and Methods: Analysis of 181 neck FNAB performed in Hospital Prof. Doutor Fernando Fonseca between 2011-216. Results: The diagnostic sensitivity and specificity of FNAB for detection of malignant disease was 88.6% and 96%. The sensitivity for detection of squamous cell carcinoma was 100%, non-squamous cell carcinoma 86.2% and lymphoproliferative disorders 86.4%. The sensitivity for detecting malignant disease in patients under 40 years of age was 77%. Conclusion: FNAB is a reliable method in the diagnosis of neck masses given its excellent parameters of diagnostic validity. However, the sensitivity for detecting malignant disease in patients under 40 years of age is lower, since in this population the proportion of patients with lymphoproliferative disorders is higher and FNAB has a lower diagnostic sensitivity for these entities.